Structured Games: Physical Activities to Develop Children's Balance Abilities - Luthfi Aji Ramdani; Imah Mulyaningsih (Yayasan Insan Mulia Bima, 2024)
This research uses quantitative research methods with a pre-experimental research design which goes through two stages, namely the pre-test and post-test stages. Which aims to measure static balance and dynamic balance abilities in children aged 4-5 years through structured games activities in 30 children. The results of this study show that the balance ability of children aged 4-5 years increased after treatment. Playing structured games has an influence on children's balance abilities at RA Darussalam Purwodeso. The pre-test showed that the child's balance ability had not developed optimally. Then treatment was carried out through playing structured games for 2 days, followed by a post-test. The post-test results show that the child's balance ability improved after being given treatment, this can be seen from the increase in the scores obtained.